2020
DOI: 10.24198/jaki.v5i1.26523
|View full text |Cite
|
Sign up to set email alerts
|

Kandungan Timbal dan Kadmium pada Air dan Sedimen di Perairan Pulau Untung Jawa, Jakarta

Abstract: Pulau Untung Jawa merupakan salah satu pulau pemukiman dan pulau destinasi wisata di Kepulauan Seribu, Jakarta. Adanya aktivitas lalu lintas kapal, perbaikan kapal, dan proyek reklamasi pantai yang ada di Pulau Untung Jawa berpotensi mencemarkan air dan tanah disekitarnya sehingga menurunkan kualitas lingkungan di Pulau Untung Jawa. Penelitian mengenai kandungan logam berat timbal (Pb) dan kadmium (Cd) yang ada di air dan sedimen yang ada di Pulau Untung Jawa dilakukan untuk mengetahui seberapa besar kandungan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
(12 reference statements)
0
5
0
8
Order By: Relevance
“…Additionally, another factor that degrades DNA in the environment is geographical conditions, in which Jakarta Bay Water is shallow water with an average depth of 15 meters, resulting in the mixing of various nutrients with pollutants and genetic material (Koropitan et al 2009). Untung Jawa Island, which is located in Jakarta Bay and relatively close to Tanjung Priok Port, also has poor water conditions (Mu ih et al 2015), one of the indicators is heavy metals which have exceeded the seawater quality standard set by the Decree of the State Minister of the Environment Number 51 of 2004 concerning Seawater Quality Standards (Alisa et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another factor that degrades DNA in the environment is geographical conditions, in which Jakarta Bay Water is shallow water with an average depth of 15 meters, resulting in the mixing of various nutrients with pollutants and genetic material (Koropitan et al 2009). Untung Jawa Island, which is located in Jakarta Bay and relatively close to Tanjung Priok Port, also has poor water conditions (Mu ih et al 2015), one of the indicators is heavy metals which have exceeded the seawater quality standard set by the Decree of the State Minister of the Environment Number 51 of 2004 concerning Seawater Quality Standards (Alisa et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have been reviewed by Alisa et al (2020) on the Coast of Untung Jawa Island, Jakarta using the AAS method. The results of the method indicated that the Pb in the sediment ranged from 14.1176 -24.1952 mg/l so that it had exceeded the safe limit and the Cd content ranged from 1.968 -2.760 mg/l, exceeding the maximum quality standard set by ANZECC/ARMCANZ.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis show that the four studies (Table 1) conducted by Nuraini et al (2017), Natsir et al (2019), Alisa et al (2020), and Setiawan and Subiandono (2015) using the AAS method, which is to analyze elements quantitatively whose measurements are based on the absorption of light with a certain wavelength by metal atoms in a free state (Skoog et al, 2004). According to Kusnadi (2016), the AAS method determines metal and metalloid elements from the radiation absorption process by free atoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berdasarkan hasil pengamatan selama 4 tahun terakhir, Cd ditemukan paling besar pada tahun 2020. penyebabnya diduga akibat aktifitas raklamasi pantai yang sangat aktif pada tahun 2020. Hal ini didukung oleh pernyataan (Alisa et al, 2020) bahwa Kandungan Cd diperairan dapat berasal dari aktvitas reklamasi Pantai. Logam berat Cr yang ditemukan pada sedimen berkisar antara 0,01±0 mg/l hingga 26,65±5,81 mg/l.…”
Section: Logam Berat Dalam Sedimenunclassified